Proximate and Organoleptic Analysis of Crackers With The Addition of Tuna Fish Bone Meal (Thunnus sp) (Agrikan Jurnal Agribisnis Perikanan, 2021)
Solid waste from the tuna fish processing industry produces a very abundant amount of waste and has not been utilized properly, even though one type of waste, namely fish bones, has high proximate nutritional content. Tuna fish bone meal is one of the uses fish bone waste treatment which is suitable as additional ingredient for making crackers to add proximate value to the product. Therefore, a study was conducted to determine the proximate and organoleptic content of crackers with the addition of tuna fish bone meal. From this study, the highest organoleptic (hedonic) test results were obtained in the addition of 5% tuna fish bone meal, then proximate test was carried out with a water content value of 7.89%, ash content 23.26%, fat content 5.21%, carbohydrate content is 58.4% and protein content is 5.24%. While the crackers without the addition of tuna bone meal had a water content of 7.40%, ash content of 14.06%, fat content of 4.21%, carbohydrate content of 70.86% and protein content of 3.47%. These results indicate that the proximate content, especially protein, fat and mineral content in the crackers with the addition of tuna is higher than the crackers without the addition of tuna bone meal.
Keywords: Analisis proksimat; organoleptik; kerupuk; tulang ikan tuna; tepung tulang ikan tuna